ANALISA ALGORITMA EXPONENTIAL SMOOTHING UNTUK SISTEM PERENCANAAN PRODUKSI KAIN BATIK DI UKM BATIK TINCTORI NATURAL DYE JAMBU - Robby Andika Kusumajaya; agustinus budi santoso (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2019)
Abstract Digital information in the economic science developed in the upstream and downstream sectors. Developments are followed by many UKM using digital technology in marketing. The forecasting uses the Exponential Smoothing algorithm Exponential Smoothing method is a procedure of continuous repairs on the latest forecasting of data. UKM Batik Tinctori Natural Dye is one of the batik producers who produce batik from customer orders and fulfill distributor requests from batik trendsThe demand of customers and distributors has an effect on the number of production batik of Tinctori Natural Dye UKM which has resulted in any batik trend that is in demand in the following month. Forecasting is calculated using the Exponential Smoothing method and Eviews software and manual comparison to lead the accuracy of the forecasting value. This prediction can be used to predict the production of batik types from the demands of consumers and distributors. Forecasting uses several methods to make predictions using different alpha and beta constants. The Comparisons of forcasting for next three months 13, 14, 15 and forecast comparisons of original values by forecasting data that already exists three months before 10, 11, 12 to find better constants that can approach the original values.